Salt above gold, and other Bohemian folk stories - Offer, Charles K. (F. Watts, 1968)
Six folktales from Bohemia: Salt above Gold; Lillybelle; Lady Luck and Mistress Misery; The Magic Pot; Alms; and Princess Ravenlocks.